Atlantis 2000. (Hannover : Deutsche Messe AG, 1989)
Bauermeister, Mary ; Fabro, Luciano ; Jaar, Alfredo ; Jankilevskij, Vladimir ; Wolf, Rita ; Krier, Leon ; Forstbauer, Nikolai B. ; Hocks, Teun ; Lauro, Anne ; Page, Robin ; Rossberg, Sarah ; Schult, HA ; Siopsis, Penelope ; Insam, Ernst ; Dossi, Ugo ; Müller, Hans-Jürgen ; Paik, Nam June ; Eggenschwiler, Franz ; Bialas, Martin ; Webb, Boyd ; Aeppli, Eva
+ 1 affiche + Atlantis Information, Antworten
Atlantis 2000, Tages-Centrum Messe Hannover, Deutsche Messe AG, Hannover. 11.06.1989 tot 14.06.1989, internationaal congres rond het Atlantis 2000-project van Hans-Jürgen Müller
kunstcatalogus